2009
DOI: 10.1055/s-0029-1191795
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ECM proteins fibulin-1 and -2 in acute and chronic liver disease and in cultured rat liver cells

Abstract: Fibulin-2 has previously been considered as a marker to distinguish rat liver myofibroblasts from hepatic stellate cells. The function of other fibulins in acute or chronic liver damage has not yet been investigated. The aim of this study has been to evaluate the expression of fibulin-1 and -2 in models of rat liver injury and in human liver cirrhosis. Their cellular sources have also been investigated. In normal rat liver, fibulin-1 and -2 were both mainly present in the portal field. Fibulin-1-coding transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
(75 reference statements)
3
6
0
1
Order By: Relevance
“…In cirrhotic liver, COL15A1 was expressed together with α‐SMA in cells thus identified as PMFs that were outlining capillaries within large fibrotic septa. Likewise, fibulin‐2, previously used as a marker of PMFs, has been shown to colocalize with vWF along vessels running in the large septa of fibrotic livers . We also found a perivascular distribution of fibulin‐2 in cirrhotic livers, although the area of fibulin‐2 staining in these tissues was largely extracellular and more extensive than that of COL15A1.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In cirrhotic liver, COL15A1 was expressed together with α‐SMA in cells thus identified as PMFs that were outlining capillaries within large fibrotic septa. Likewise, fibulin‐2, previously used as a marker of PMFs, has been shown to colocalize with vWF along vessels running in the large septa of fibrotic livers . We also found a perivascular distribution of fibulin‐2 in cirrhotic livers, although the area of fibulin‐2 staining in these tissues was largely extracellular and more extensive than that of COL15A1.…”
Section: Discussionsupporting
confidence: 67%
“…F and http://onlinelibrary.wiley.com/doi/10.1002/hep.27318/suppinfo, right‐upper panel). We also performed experiments to determine how COL15A1 compared with fibulin‐2, a previously used marker of PMFs . We confirmed, by RT‐PCR analyses, that Col15a1 was more discriminant than fibulin‐2 to distinguish PMFs from HSC‐MFs (http://onlinelibrary.wiley.com/doi/10.1002/hep.27318/suppinfo).…”
Section: Resultssupporting
confidence: 52%
“…INK4A (CDKN2A), which belongs to the family of cyclin-dependent kinase inhibitors, leads to cell cycle arrest in the G1 phase by causing the inhibition of cyclin D-dependent kinases [74]. Fibulin-1(FBLN1) belongs to an enormous family of plasma glycoprotein and will be significantly increased in acute liver injury [75].…”
Section: Gene Methylation Alterationsmentioning
confidence: 99%
“…Perhaps epidermal dendritic cells are critical producers of TGF-β1 in Tsk2/+ skin (Gruschwitz and Hornstein, 1992). The proposed causal relationship of TGF-β1 to skin fibrosis and the physical phenotype of tight skin in Tsk2/+ mice needs verification, but we note that at two weeks, skin from male Tsk2/+ mice expresses 170%-300% more mRNA for five TGF-β1 signature proteins (collagen type V, alpha 2; elastin; fibulin-2; α-smooth muscle actin; and cartilage oligomeric protein) (Piscaglia et al, 2009;Kurpinski et al, 2010;Sargent et al, 2010) as assessed by quantitative real-time PCR (data not shown).…”
Section: Discussionmentioning
confidence: 80%